2016
DOI: 10.1111/epi.13394
|View full text |Cite
|
Sign up to set email alerts
|

Kainic acid–induced albumin leak across the blood–brain barrier facilitates epileptiform hyperexcitability in limbic regions

Abstract: Dr. Francesco M. No e is a researcher with experience in EEG and animal models of epilepsy. SUMMARYObjective: Systemic administration of kainic acid (KA) is a widely used procedure utilized to develop a model of temporal lobe epilepsy (TLE). Despite its ability to induce status epilepticus (SE) in vivo, KA applied to in vitro preparations induces only interictal-like activity and/or isolated ictal discharges. The possibility that extravasation of the serum protein albumin from the vascular compartment enhances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
(105 reference statements)
2
13
0
Order By: Relevance
“…15,31 Furthermore, serum albumin uptake by astrocytes through the transforming growth factor β receptors (TGF-β Rs), has been linked to a rapid downregulation of astrocytic K + -inward-rectifying (K IR ) channels, resulting in a reduced buffering and subsequent accumulation of potassium in the extracellular space and in an increased brain excitability. 32 In our experimental conditions, 15 hALB is perfused at 4 mg/mL, which falls within the range associated with BBB damage occurring in a pathology associated condition. 33 Co-perfusion of LPS, hALB, and na-PBMCs (and autologous resting guinea pig splenocytes) never generated SLEs or microgliosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15,31 Furthermore, serum albumin uptake by astrocytes through the transforming growth factor β receptors (TGF-β Rs), has been linked to a rapid downregulation of astrocytic K + -inward-rectifying (K IR ) channels, resulting in a reduced buffering and subsequent accumulation of potassium in the extracellular space and in an increased brain excitability. 32 In our experimental conditions, 15 hALB is perfused at 4 mg/mL, which falls within the range associated with BBB damage occurring in a pathology associated condition. 33 Co-perfusion of LPS, hALB, and na-PBMCs (and autologous resting guinea pig splenocytes) never generated SLEs or microgliosis.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, BBB permeability leads to the extravasation into the brain parenchyma of serum proteins and immune cells, triggering inflammation and ictogenesis. Serum albumin extravasation, due to its negative charge, alters the neuronal membrane charge, contributing to an acute increase in neuronal excitability 30 and, at the same time, is able to disrupt the neuronal and glial membrane homeostasis 15,31 . Furthermore, serum albumin uptake by astrocytes through the transforming growth factor β receptors (TGF‐β Rs), has been linked to a rapid downregulation of astrocytic K + ‐inward‐rectifying (K IR ) channels, resulting in a reduced buffering and subsequent accumulation of potassium in the extracellular space and in an increased brain excitability 32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies have confirmed that BBB is an important barrier to the central nervous system (CNS) (Friedman & Kaufer 2015). In epilepsy (Noe et al . 2016), Alzheimer’s disease (Lecler et al .…”
Section: Discussionmentioning
confidence: 99%